Management of Treatise Conference Information System (SIFASRAPI) DPRD Secretariat of North Sulawesi Province - Hamonsina, Jerry K; Masengi, Evi E.; Tumbel, Goinpeace H. (International Journal of Information Technology and Education, 2024)
The aim is to find out the management of SIFASRAPI at the DPRD Secretariat of North Sulawesi Province, specifically in the Session Section of the DPRD of North Sulawesi Province. This research uses a descriptive method with a qualitative approach. Data collection techniques include observation, interviews, and documentation methods. Data processing techniques with stages of data reduction, data presentation, and verification. This research highlights the management of the Session Minutes Information System (SIFASRAPI) at the DPRD Secretariat of North Sulawesi Province, both in the planning, budgeting, and reporting or evaluation processes. SIFASRAPI encountered obstacles, including problems with human resources, supporting facilities, and infrastructure such as the internet network and the imperfect SIFASRAPI application, which became an obstacle to the implementation of SIFASRAPI at the DPRD Secretariat of North Sulawesi Province. Based on the results of the research conducted, it can be concluded that SIFASRAPI management at the DPRD Secretariat has been running well and it is recommended that the Regional Government increase the capacity of Human Resources, repair, and increase supporting facilities and infrastructure as well as for the Provincial Government to help provide input for the development of the SIFASRAPI Application.